An overview of the Knowledge of Level 1 Nurse Students about the 5M Health Protocol in Covid-19 Prevention at STIKes Santa Elisabeth Medan 2022 - Rusmauli Lumban Gaol; Juliana Naibaho (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
Background: The 5M health protocol is a complement to the 3M, namely wearing masks, washing hands, keeping a distance to avoid crowds and reducing mobility which has been initiated by the government. This effort demands high discipline and must be applied consistently at all times. The problem involved in this research is regarding the 5M health protocol, where if someone does not carry out the 5M then positive cases of covid-19 will continue to increase in the community. So to overcome this, it is recommended for students to carry out the 5M movement, especially at STIKes Santa Elisabeth Medan to prevent the spread of covid-19. Knowledge is the result of sensing activities through the five senses such as smell, taste, touch and hearing. Objective: This study aims to describe the knowledge of level 1 nurse students about the 5M health protocol in preventing Covid-19 at STIKes Santa Elisabeth Medan in 2022. Methods: The method used in this study was descriptive, the number of respondents was 85 people. The sampling technique used a total sampling technique, namely the number of respondents at STIKes Santa Elisabeth Medan amounted to 85 respondents. The results showed that the 5M Health Protocol at STIKes Santa Elisabeth Medan from 85 respondents was good as many as 84 people (98.8%) and only 1 person (1.2%). Conclusion: It can be concluded that the majority of respondents have good knowledge in implementing the 5M health protocol in preventing Covid-19 84 respondents (98.8%) and only 1 respondent (1.2%). Suggestion: it is hoped that all students, especially level 1 nurses, so that the 5M health protocol needs to be improved to prevent the spread of covid-19.